Model induction from data: towards the next generation of computational engines in hydraulics and hydrology - Dibike Yonas Berhan (Lisse Swets & Zeitlinger, 2002)
This thesis addresses model induction from data for the simulation of hydrodynamic processes in the aquatic environment. It introduces some popular artificial neural network architectures from different aspects and its applications such as multi-layer per
Keywords: Hydraulic engineering; Hydrology